A Sex Disparity Among Earthquake Victims. (2nd July 2015) - Ardagh, Michael; Standring, Sarah; Deely, Joanne M.; Johnston, David; Robinson, Viki; Gulliver, Pauline; Richardson, Sandra; Dierckx, Alieke; Than, Martin
Abstract: Objective: Understanding who is most vulnerable during an earthquake will help health care responders prepare for future disasters. We analyzed the demography of casualties from the Christchurch earthquake in New Zealand. Methods: The demography of the total deceased, injured, and hospitalized casualties of the Christchurch earthquake was compared with that of the greater Christchurch population, the Christchurch central business district working population, and patients who presented to the single acute emergency department on the same month and day over the prior 10 years. Sex data were compared to scene of injury, context of injury, clinical characteristics of injury, and injury severity scores. Results: Significantly more females than males were injured or killed in the entire population of casualties ( P <0.001). Most of the deceased and hospitalized casualties were injured in the central business district (171/182 deceased [94%]; 33/91 hospitalized [36.2%]). Approximately half of both sexes were injured at home (1002/2032 males [49%]; 2390/4627 females [52%]) and >20% were injured at commercial or service localities (444/2032 males [22%]; 1105/4627 females [24%]). Adults aged between 20 and 69 years (1639/2032 males [81%]; 3717/4627 females [80%]) were most frequently injured. Conclusion: Where people were and what they were doing at the time of the earthquake influenced their risk of injury. ( Disaster Med Public Health Preparedness . 2016;10:67-73)